Electrical Resistivity and Magnetoresistance Properties of Cation A-site substitution in La0.8-xAgxCa0.2MnO3 (x = 0.1 and 0.15) - Dicky Rezky Munazat; Budhy Kurniawan; Rina Kamila; Maykel Manawan; Agung Imaduddin (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
The polycrystalline sample of La0.8-xAgxCa0.2MnO3 (x = 0.1 and 0.15) has been successfully synthesized using a sol-gel method in our previous work. Here, we have investigated the electrical resistivity and magnetoresistance of both samples. All samples exhibited metallic behavior, as evidenced by the resistivity data measured in the temperature range from 9 to 285 K. As silver concentration increases, the resistivity decreases throughout the whole explored temperature range. Increasing silver ion concentration improves double exchange interaction (DE) between Mn3+ and Mn4+ which is responsible for gradually decreasing resistivity. The electrical transport is quite well described by a theory based on grain boundary factor, electron-electron interaction, and Kondo-like spin-dependent scattering mechanisms. Both samples show low-field magnetoresistance (LFMR) at low temperatures. The maximum magnetoresistance values for both samples were observed at 15 K, with values of -23.16% and -25.17% for x = 0.10 and 0.15, respectively.